DNA barcoding identifies a third invasive species of Eleutherodactylus (Anura: Eleutherodactylidae) in Panama City, Panama - Crawford, Andrew J.; Alonso, Roberto; A., César A. Jaramillo; Sucre, Samuel; D., Roberto Ibáñez (Zootaxa, 2011)
Eleutherodactylus planirostris Cope 1862, the greenhouse frog, is native to the Bahamas, Cayman Islands and Cuba, with introduced populations in the southeastern United States, Jamaica, Honduras, Mexico, Grenada, Caicos Islands, the Miskito Cays of Nicaragua, and on the Pacific islands of Hawaii and Guam (Heinicke et al. 2011; Somma 2011). This species was not previously recorded in the Republic of Panama, although two other invasive Eleutherodactylus species, E. antillensis Reinhardt & Lütken 1863 1862 and E. johnstonei Barbour 1914, have established populations within Panama City (Jaramillo et al. 2010). Based on standardized mitochondrial gene fragments, we report for the first time the presence of E. planirostris in Panama.